Mewahang Verbs and the Proto-Kiranti Verbal Agreement System - Sharma, Narayan P. (Nepalese Linguistics, 2022)
The purpose of this paper is to overview the historical status of conjugations observed in the Mewahang language based on a comparison of Proto-Kiranti verbal agreement system. The provenance of Proto-Kiranti affixal agreement paradigms is presented by investigating the conjugations of Mewahang. While some Mewahang suffixes are identical with the Proto-Kiranti morphemes, a few are cognate with the Proto-Kiranti reflexes.